Pre-service ESL teachers' perceptions of parody integration in digital stories - Abdul Latiff, Azmi; Mat Daud, Nuraihan (IDOSI Publication, 2013)
Advancement in digital technology has led to the increase in popularity of digital videos. Online videos are easily accessible to users through Youtube and similar networks. The language learning and teaching field in particular has also benefitted from the technological advancements in digital video production. One of its uses is in the teaching of language through humour. The use of digital videos could help create a humorous atmosphere in the class. Substantial number of research has been conducted on the use of humor in language classes but most of them are based on printed materials. This study attempts to use the videos on Youtube to create parody as a means of developing their language skills. It seeks to investigate students’ perception of integrating elements of humour in the digital stories. The study aims to capture the language of humor used by the students through the videos that they produced. In order to do this, a group of ESL pre-service teachers were given the task to produce a humorous video-based (on Youtube) digital story. Self-administered online questionnaire was used to elicit their responses. Overall, most of the teacher trainees gave positive feedback to the given task. From the pedagogical perspective, the research concludes that producing humorous video-based digital story could be used to improve students’ language skills.